ANALISIS NILAI PENDIDIKAN DALAM BUKU ANTOLOGI CERPEN GADIS PAKARENA - Dita Anggriani (Universitas Negeri Makassar, 2020)
Analysis of Educational Values in Gadis Pakarena Short Story Anthology Book. This research is to study the educational values in the short story anthology book of Gadis Pakarena by Krisna Pabichara. This type of research is a qualitative descriptive study. The data source of this research is the anthology of Gadis Pakarena short story by Khrisna Pabichara consisting of seven short stories, entitled: Gadis Pakarena, Arajang, Rumah Panggung di Kaki Bukit, Haji Baso, Silariang, Ulu Badik Ulu Hati dan Pembunuhan. The results of the study that showed the educational value contained in the anthology of Gadis Pakarena short stories, among others: trust, patience, honesty, filial piety for parents, wise and hard work.